PENTINGNYA PSIKOLOGI PENDIDIKAN BAGI GURU - Rudi Haryadi; Cindi Cludia (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Educational psychology learning means studying the psychological aspects of students so that the teacher has basic rules for applying effective learning techniques that are applied to certain student characteristics. Learning skills also involve communicated strategies in learning, regardless of whether students understand them well or not. In the educational process, a teacher is expected to face challenges in evaluating the different characteristics of each student. In educational psychology, the teacher will understand the differences in student personalities in learning and how to deal with these personality differences, so that by studying good educational psychology, the teacher can know the differences in student character and not be confused in dealing with them. In educational psychology, there is a lot of discussion about problems related to human development. Therefore, teachers can not only teach thematic subjects in the classroom, but also provide direction or guidance to students who need academic problems. In addition to providing solutions for students who have academic problems, teachers can also build social bonds with students so as to create a positive atmosphere in learning activities.